Contributions to the self-care of men with systemic arterial hypertension in primary health care - Ribeiro, Wanderson Alves; Santos, Larissa Christiny Amorim dos; Castro, Kemely de; Dias, Lilian Laine da Conceição; Morais, Maicon Costa de; Ribeiro, Matheus Sampaio; Cirino, Hosana Pereira; Freire, Maria Júlia Louvain Longo (Brazilian Journal of Science, 2022)
The male gender is more susceptible to acquiring cardiovascular diseases, respiratory diseases, cancers, among others, due to the indiscriminate use of legal substances and tobacco. Due to this, greater vulnerability and high rates of morbidity and mortality, it is proven that, unlike women, men do not seek primary health care services. It is therefore necessary to better understand the context related to the male gender, aiming to promote their health. This is an integrative literature review study, which followed the stages of elaboration of an integrative review, in the databases of Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and with a time record from 2018 to 2022. It is concluded that self-care as an approach for the male public still shows a great deficit in the strategy addressed by them, also showing that systemic arterial hypertension is a major health problem, which ends up affecting men over 40 years old, because in their youth they do not seek self-care and no screening in PHC, with this distance in primary care, men end up being more likely to develop cardiovascular diseases and thus die early. Where a nurse in primary health care is the professional capable of contributing to promotion and prevention through health education, aiming to encourage this hypertensive man to perform daily self-care.